Analysis of Accounts Receivable Turnover at PT. The Core of Sumatran Success in 2021 - Zulhendra, Zulhendra; Lady Novica (Dinasti International Journal of Economics, Finance & Accounting, 2021)
This study aims to analyze how big the level of receivables turnover on sales made by PT. Inti Sukses Sumatera in 2021. In the midst of intense business competition, companies are required to be able to achieve market position, so companies need to carry out a credit sales strategy, so that the number of sales increases. Receivables in general can be defined as claims or arising from the sale of goods or services on credit with a predetermined period of time as a result of credit sales. Receivables are a type of current asset listed on the balance sheet. Receivables can be potential if managed properly but otherwise will be a risk if not managed properly. The research method used is descriptive quantitative method, namely research that uses numerical data (numbers), which is then processed and analyzed to draw conclusions. Data collection techniques used are interviews and documentation. From this data is analyzed using ratio analysis, especially those related to receivables turnover rate, receivable collection period, arrears ratio and billing ratio. The results of the study are: (1) The ratio of the receivables turnover rate of PT. Inti Sukses Sumatera during the first semester of 2021 was 8 times and the second semester decreased to 7 times, so that the collection made by management is considered successful, (2) in the first semester the average collection period of receivables is 43 days in the first six months of the year. 2021. In the second semester the average collection of receivables at PT Inti Sukses Sumatra during 2021 is slower to 52 days, so it can be said that the company is able to collect on time, (3) that the ratio of arrears is 1.180% in the first semester and second semester of 0.97%. Arrears of more than 1% occur in the first semester and can harm the company because the funds that should be revolving will remain embedded in receivables, (4) the above collection ratio in the first six months of 2021 is 98.83 and 99.04% in the second semester . So that the company is able to do well in collecting receivables.